2007
DOI: 10.1038/nrg2072
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements and the epigenetic regulation of the genome

Abstract: Overlapping epigenetic mechanisms have evolved in eukaryotic cells to silence the expression and mobility of transposable elements (TEs). Owing to their ability to recruit the silencing machinery, TEs have served as building blocks for epigenetic phenomena, both at the level of single genes and across larger chromosomal regions. Important progress has been made recently in understanding these silencing mechanisms. In addition, new insights have been gained into how this silencing has been co-opted to serve ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
1,539
2
18

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,752 publications
(1,628 citation statements)
references
References 144 publications
21
1,539
2
18
Order By: Relevance
“…Transposable elements were first reported in maize 19 and have since been shown to have important roles in shaping genome evolution and gene regulatory networks of many species 20 . Most of the maize Letter reSeArCH genome is derived from transposable elements 3, 21 , and careful study of a few regions has revealed a characteristic structure of sequentially nested retrotransposons 21,22 and the effect of deletions and recombina tion on retrotransposon evolution 23 .…”
Section: Openmentioning
confidence: 99%
“…Transposable elements were first reported in maize 19 and have since been shown to have important roles in shaping genome evolution and gene regulatory networks of many species 20 . Most of the maize Letter reSeArCH genome is derived from transposable elements 3, 21 , and careful study of a few regions has revealed a characteristic structure of sequentially nested retrotransposons 21,22 and the effect of deletions and recombina tion on retrotransposon evolution 23 .…”
Section: Openmentioning
confidence: 99%
“…(60) It is not known how cells recognize newly transposed elements and induce chromatin and DNA methylation but, in some eukaryotic organisms (S.pombe, C.elegans, D.melanogaster, A.thaliana), duplex RNA formed by transcripts from both strands of RT is cleaved with specific RNase III (DICER) and the resulting small RNAs (<30 nt) are captured by complexes containing an ARGONAUTE (Ago) protein, which either induce cleavage of RT transcripts (RISC complexes) or induce histone H3 methylation at lysine-9 in chromatin and de novo DNA methylation of RT genomic sequences (RITS complexes) (reviewed in Ref. 23). Although this RNA interference (RNAi)-mediated RT silencing is not yet established in mammalian cells, LINE1-encoded RNA-binding protein ORF1p colocalizes at cytoplasmic stress granules in human cells with components of the RISC complex (Ago2, FMRP) suggesting that mammalian retrotransposition can be also controlled by RNAi.…”
Section: Modulation Of Biological Effects Of Retroelements By Their Ementioning
confidence: 99%
“…Epigenetic silencing of non-mutated retrotransposons (''genome defense'') in many non-mammalian animals and plants can be also achieved without their methylation through the mechanism of RNA interference. (23) The vast majority of genomic copies of retroelements is already mutated and retropositionally inactive, so their continuous methylation is not required for repression of retroposition. A protein that binds to methyl-CpG (MeCP2) and that can mediate effects of DNA methylation has been identified.…”
Section: Modulation Of Biological Effects Of Retroelements By Their Ementioning
confidence: 99%
See 2 more Smart Citations